Analysis of discard of whole blood and its components with suggested possible strategies to reduce it - Patil, Parikshit; Bhake, Arvind; Hiwale, Kishor (International Journal of Research in Medical Sciences, 2016)
Background: Advances in medical technology demand more and more provision of safe blood for effective management of patients. To tackle with the demand and supply of blood and blood components, more stringent criteria should be applied for blood donations and for proper utilization of blood. The present study was designed to analyze the various reasons for the discard of whole blood and blood components. It also intended to suggest various possible strategies for optimum utilization of blood and reduction of wastage. Methods: In this retrospective study we analyzed various causes of discard of blood and blood components from January 2013 to June 2015 (30 months) using various records available in the blood bank of Jawaharlal Nehru Medical college and Acharya Vinoba Bhave Rural Hospital, Sawangi, Wardha, Maharashtra, India. Results: A total of 14,026 blood bags were collected during the study period of 30 months, out of which 9,785 were whole blood while components were prepared from remaining blood bags. A total of 3,944 Packed Red Cells, 2,137 Platelet Concentrate and 3,944 Fresh Frozen Plasma were prepared. Average discard rate was found to be 22.45% while discard rate for Whole blood, Packed Red Cells, Platelet Concentrate and Fresh Frozen Plasma were 07.70%, 06.74%, 61.11% and 14.24% respectively. Conclusions: Platelets were the most commonly discarded blood component due to short shelf life and non utilization in time as demand cannot be predicted. In our study the main reason for discarding whole blood and Packed Red Cells was sero-positivity for various Transfusion Transmitted Infections while non utilization after issue, breakage/leakage were the main reasons for Fresh Frozen Plasma discard. The self audit of blood transfusion service provides insight into current blood transfusion practices prevalent in the hospital.